2023
DOI: 10.2138/am-2022-8257
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Al2O3 on the structural properties of MgSiO3 akimotoite

Abstract: Akimotoite, a MgSiO3 polymorph, present in the lower transition zone within ultramafic portions of subducting slabs and potentially also in the ambient mantle, will partition some amount of Al, raising the question of how this will affect its crystal structure and properties. In this study, a series of samples along the MgSiO3 akimotoite -Al2O3 corundum solid solution have been investigated by means of single-crystal X-ray diffraction in order to examine their crystal chemistry. Results show a strong non-linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Both theoretical and experimental studies indicate that the incorporation of Al in the structure of akimotoite produces a decrease of its unit‐cell volume (Panero et al., 2006; Siersch, 2019). The unit‐cell volume of akimotoite in our experiment is also smaller compared to the unit‐cell volume of akimotoite with 20 mol % Al 2 O 3 (Siersch, 2019) (Figure 3a). Our interpretation is that the Al content in our akimotoite is higher than 20 mol%: if during the decomposition of Al‐bearing shy‐B all the Al released from shy‐B dissolves in the structure of akimotoite, the Al 2 O 3 content in akimotoite would be 23.8 mol% with a (Mg 0.763 Al 0.238 ) (Al 0.238 Si 0.763 )O 3 composition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both theoretical and experimental studies indicate that the incorporation of Al in the structure of akimotoite produces a decrease of its unit‐cell volume (Panero et al., 2006; Siersch, 2019). The unit‐cell volume of akimotoite in our experiment is also smaller compared to the unit‐cell volume of akimotoite with 20 mol % Al 2 O 3 (Siersch, 2019) (Figure 3a). Our interpretation is that the Al content in our akimotoite is higher than 20 mol%: if during the decomposition of Al‐bearing shy‐B all the Al released from shy‐B dissolves in the structure of akimotoite, the Al 2 O 3 content in akimotoite would be 23.8 mol% with a (Mg 0.763 Al 0.238 ) (Al 0.238 Si 0.763 )O 3 composition.…”
Section: Resultsmentioning
confidence: 99%
“…The unit‐cell volume of akimotoite, formed during decomposition of Al‐bearing shy‐B, is 1.6% smaller than that of Al‐free akimotoite (Wang et al., 2004). Both theoretical and experimental studies indicate that the incorporation of Al in the structure of akimotoite produces a decrease of its unit‐cell volume (Panero et al., 2006; Siersch, 2019). The unit‐cell volume of akimotoite in our experiment is also smaller compared to the unit‐cell volume of akimotoite with 20 mol % Al 2 O 3 (Siersch, 2019) (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggested that the velocities and density of the pyrolite model can match the one-dimension (1D) seismological models such as PREM [2] and AK135 [3] for the upper mantle [4] and the lower mantle [ 5 , 6 ]. However, the shear wave velocity and density of the pyrolite model are lower than PREM or AK135 up to 4% and 2% in the lower mantle transition zone (MTZ) [7] , [8] , [9] . Based on the complicated slab dynamics in the lower MTZ, different hypotheses including the enrichment of harzburgite-rich materials were introduced to reconcile this discrepancy [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 91%